Analisis Strategi Problem - Based Learning (PBL) Dalam Mengembangkan Dimensi “Bernalar Kritis” Pada Profil Pelajar Pancasila Dalam Pembelajaran IPS - Mamduh Rusydan; Muhammad Ali Wafa; Maulfi Fahrul Fahani; Muhammad Jimly Assiddiqie; Ahmad Rosikhul Fahmi (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
This study aims to conceptually analyze the strategic role of Problem-Based Learning (PBL) in developing the Critical Reasoning dimension of the Pancasila Student Profile in the context of Social Studies (IPS) learning. Amidst the challenges of IPS learning which tends to be theoretical and passive, the Independent Curriculum demands an innovative, student-centered approach. Using a qualitative literature study method, this study examines and synthesizes various scientific sources to map the alignment between the syntax (stages) of PBL and the key elements of critical reasoning skills. The analysis results show that each phase in PBL from problem orientation, learning organization, investigation, presentation of results, to process evaluation is systematically designed to train students in acquiring and processing information, analyzing reasoning, reflecting on thoughts, and making decisions. PBL creates a learning ecosystem that not only addresses the issue of the relevance of IPS material by presenting it in a real-world context, but also inherently stimulates the development of other dimensions of the Pancasila Student Profile such as mutual cooperation, independence, and creativity. It is concluded that PBL is a highly aligned and effective pedagogical framework for implementing the objectives of the Independent Curriculum, particularly in producing a generation capable of critical thinking in facing the complexities of the times.